Sexualidad y Comunicación en la Pareja (2021)
Sexuality and communication in the couple are elements that are part of the daily life of human beings showing that when living with a partner or spouse there must be an assertive communication, a respectful dialogue, listening to the other and respecting his or her opinion, also the sexual life that one has must be taken into account and thus allow the couple's relationship to be lasting, to reflect respect, to reach healthy agreements for both parties and to be a healthy relationship.